Twelve-Week MSRT Effects on Heart Rate, Blood Pressure and Sleep Quality in Injured National Athletes - Saha, Sohom; Singh, Harish; Thomas, Cicelia Mohan; Khati, Awesh; Karmakar, Debajit (Фізична реабілітація та рекреаційно-оздоровчі технології, 2025)
Purpose. Athletic injuries often lead to both physiological and psychological impairments, necessitating holistic rehabilitation strategies. Mind Sound Resonance Technique (MSRT), is a yoga-based meditative technique, that has shown promise in enhancing autonomic regulation and psychological resilience. However, its impact on cardiovascular health and sleep quality in injured athletes remains unexamined. This study aimed to examine the effects of a 12-week MSRT intervention on heart rate, blood pressure, and sleep quality in national-level injured athletes. Materials and methods. A randomized controlled trial was conducted with 36 injured athletes (aged 18-25 years) assigned to either a Yoga Practice Group (YPG) and a Control Group (CG). The YPG underwent supervised MSRT sessions for 12 weeks, while the CG followed their standard rehabilitation routine. Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), and sleep quality (SQ) were assessed at baseline, 4th, 8th, and 12th weeks using validated instruments, including the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using Repeated Measures ANOVA. Results. Significant time × group interaction effects were observed in HR (F=87.44, p<0.001, η²p=0.72), SBP (F=42.06, p<0.001, η²p=0.55), DBP (F=48.76, p<0.001, η²p=0.58), and SQ (F=71.31, p<0.001, η²p=0.67). The YPG exhibited a notable decrease in HR (62.88±1.49 bpm to 55.44±1.46 bpm), SBP (124.27±1.48 mmHg to 120.61±0.69 mmHg), and DBP (84.11±0.75 mmHg to 80.55±0.61 mmHg). Sleep quality improved significantly (PSQI: 17.27±0.89 to 11.44±1.04, p<0.001), whereas the CG showed minimal changes. Conclusions. The findings suggest that MSRT is an effective adjunct to conventional rehabilitation, promoting cardiovascular recovery and sleep enhancement in injured athletes. Future studies should explore the sustained effects of MSRT benefits over time and its relevance to various injury profiles.